Key issues and countermeasures of coal mine water treatment and recycling - XUE Gang; LIU Jianqi; QIANG Zhibin; WANG Yonggang; GUO Yao; CHEN Hong (Gongye shui chuli)
Coal mine water with large volume and relatively clean quality, can be used as unconventional water resources. However, there is a common problem of low resource utilization ratio in coal mine water. From the perspective of treatment technology, comprehensive recycling mode and technical standard system, the restraints of coal mine water recycling were dissected. For the treatment of mine water containing suspended matter, iron and manganese, high salinity and acid, the development of low-carbon and cost technologies were expounded, such as suspended matter removal by enhanced coagulation and sedimentation, untrafiltration and microfiltration, biological iron and manganese removal, and nanofiltration membrane desalination. Technical characteristic and progress of reduction and recycling of sludge derived from mine water treatment were summarized. To address the issue that coal mine water was difficult to be completely consumed in enterprises and recycle externally, the recycling mode combining enterprise inside and outside through centralized treatment plant was proposed. Meanwhile, the prospect and feasibility of producing high-quality drinking water from mine water were analyzed preliminarily. On the basis of clarifying the current situation of the standard system for coal mine water discharge and recycling, formulating specific discharge standards, technical specifications for coal mine water recycling, sludge treatment, disposal and recycling, could boost the sustainable development of coal industry.